Characterization of Breast Lesions: Comparison of Digital Breast Tomosynthesis and Ultrasonography - Kim, Sun Ah (Korean J Radiol, 2015)
OBJECTIVE: To compare the diagnostic performance of digital breast tomosynthesis (DBT) and conventional breast ultrasound (US) to characterize breast lesions as benign or malignant. MATERIALS AND METHODS: A total of 332 women, presenting for screening examinations or for breast biopsy between March and June 2012 were recruited to undergo digital mammography (DM), DBT, and breast US examination. Among them, 113 patients with 119 breast lesions depicted on DM were finally included. Three blinded radiologists performed an enriched reader study and reviewed the DBT and US images. Each reader analyzed the lesions in random order, assigned Breast Imaging Reporting and Data System (BI-RADS) descriptors, rated the images for the likelihood of malignancy (%) and made a BI-RADS final assessment. Diagnostic accuracy, as assessed by the area under the receiver operating characteristic curve, sensitivity, and specificity of DBT and US were compared. RESULTS: Among the 119 breast lesions depicted on DM, 75 were malignant and the remaining 44 were benign. The average diagnostic performance for characterizing breast lesions as benign or malignant in terms of area under the curve was 0.899 for DBT and 0.914 for US (p = 0.394). Mean sensitivity (97.3% vs. 98.7%, p = 0.508) and specificity (44.7% vs. 39.4%, p = 0.360) were also not significantly different. CONCLUSION: Digital breast tomosynthesis may provide similar reader lesion characterization performance to that of US for breast lesions depicted on DM.